Kilabot at kembot (Quezon City Viva Video., 2002)
The murder of his long-time partner 'Kamandag'- He tried to obtain justice for his comrade but failed because the culprit was able to escape. Leon after sometime, decided to retire from being a secret agent and concentrate on his career as a tattoo artist. One day, he meets a gorgeous lady named Sienna, a college coed and immediately falls in love with her. Little did he know that Sienna is a stripteaser and she is actually the personal private dancer of Chino Guevarra, the head of a big time syndicate responsible for the series of kidnappings in the city who happens to be same person responsible for 'Kamandag' murder.
VCD
Ramon 'Bong' Revilla Jr., Assunta De Rossi, Roi Vinzon, Long Mejia
Keywords: Feature films; Action-- Drama